The design, implementation and assessing of an agroecological cropping system by rural KwaZulu-Natal households : its effect on their diet and food security - Strachan, Brian Douglas (Stellenbosch : Stellenbosch University, 2014)
Thesis(MPhil)--Stellenbosch University, 2014